Extracellular export of sphingosine kinase-1a contributes to the vascular S1P gradient - Venkataraman, Krishnan; Thangada, Shobha; Michaud, Jason; Oo, Myat Lin; Ai, Youxi; Lee, Yong-Moon; Wu, Mingtao; Parikh, Nehal S.; Khan, Faraz; Proia, Richard L.; Hla, Timothy (Biochemical journal, 2006)
Sphingosine 1-phosphate (S1P), produced by Sphks (sphingosine kinases), is a multifunctional lipid mediator that regulates immune cell trafficking and vascular development. Mammals maintain a large concentration gradient of S1P between vascular and extravascular compartments. Mechanisms by which S1P is released from cells and concentrated in the plasma are poorly understood. We recently demonstrated [Ancellin, Colmont, Su, Li, Mittereder, Chae, Stefansson, Liau and Hla (2002) J. Biol. Chem. 277, 6667–6675] that Sphk1 activity is constitutively secreted by vascular endothelial cells. In the present study, we show that among the five Sphk isoforms expressed in endothelial cells, the Sphk-1a isoform is selectively secreted in HEK-293 cells (human embryonic kidney cells) and human umbilical-vein endothelial cells. In sharp contrast, Sphk2 is not secreted. The exported Sphk-1a isoform is enzymatically active and produced sufficient S1P to induce S1P receptor internalization. Wild-type mouse plasma contains significant Sphk activity (179 pmol·min−1·g−1). In contrast, Sphk1−/− mouse plasma has undetectable Sphk activity and approx. 65% reduction in S1P levels. Moreover, human plasma contains enzymatically active Sphk1 (46 pmol·min−1·g−1). These results suggest that export of Sphk-1a occurs under physiological conditions and may contribute to the establishment of the vascular S1P gradient.